Time-resolved FTIR study of the 308 nm photolysis of NO2. Nascent vibrational populations and quenching of NO(upsilon=1-3) - Doughty, A; Hancock, G; Moore, E (1997)
The nascent distribution of the vibrationally excited NO product of NO2 photolysis at 308 nm has been determined by time-resolved FTIR spectroscopy. The percentage distribution in the excited vibrational levels ν = 1:2:3 was found to be (28 ± 3:38 ± 4:34 ± 4), with negligible population in higher levels. The distribution is inconsistent with that predicted from simple statistical theories, and indicates that at this wavelength dynamical effects control the vibrational energy partitioning. The quenching of NO(ν) by NO2 is dominated by single quantum energy transfer, but does not populate the closely resonant (0, 0, 1) level of NO2 with unit efficiency. © 1997 Elsevier Science B.V.